2016
DOI: 10.3851/imp3103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tenofovir Disoproxil Fumarate on Bone Metabolism and Bone Mass among Perinatally HIV-Infected Asian Adolescents

Abstract: Recent TDF administration was correlated with PTH elevation and bone turnover dysregulation but not with bone mass reduction in our cohort. A study with extended follow-up to ascertain TDF-associated bone mass deterioration is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…For example, among 74 Brazilian adolescents (mean age 17•3 years [SD 1 •8]), increased duration of TDF use was associated with lower (albeit non size-adjusted) lumbar spine and total body bone density; 35 whereas a larger study of 394 Thai adolescents of a similar age (median 16•1 years [IQR 14•7-17•4) found no such association for (non-size adjusted) total body bone density or (size-adjusted) LS-BMAD. 36 Our study supports the hypothesis that TDF use has a detrimental effect on bone health in children. Notably, we observed a dose response, with increased TDF exposure associated with pronounced bone deficits.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, among 74 Brazilian adolescents (mean age 17•3 years [SD 1 •8]), increased duration of TDF use was associated with lower (albeit non size-adjusted) lumbar spine and total body bone density; 35 whereas a larger study of 394 Thai adolescents of a similar age (median 16•1 years [IQR 14•7-17•4) found no such association for (non-size adjusted) total body bone density or (size-adjusted) LS-BMAD. 36 Our study supports the hypothesis that TDF use has a detrimental effect on bone health in children. Notably, we observed a dose response, with increased TDF exposure associated with pronounced bone deficits.…”
Section: Discussionsupporting
confidence: 88%
“…For example, among 74 Brazilian adolescents (mean age 17·3 years [SD 1·8]), increased duration of TDF use was associated with lower (albeit non size-adjusted) lumbar spine and total body bone density; 35 whereas a larger study of 394 Thai adolescents of a similar age (median 16·1 years [IQR 14·7–17·4) found no such association for (non-size adjusted) total body bone density or (size-adjusted) LS-BMAD. 36 …”
Section: Discussionmentioning
confidence: 99%
“…However, there are few data regarding these effects in HBV‐HIV co‐infected populations. Bone mineral turnover (BMT) markers may mediate the BMD decline observed with TDF‐containing regimens as evidenced by high BMT markers associated with bone resorption markers, PTH levels and negatively associated with bone formation markers [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that tenofovir may cause renal proximal tubule toxicity, resulting in phosphate wasting and increased bone turnover 18. Although tenofovir and protease inhibitors have been associated with low BMD in adults,19 20 studies in children have shown inconsistent findings 21–23. Malnutrition, opportunistic infections and social deprivation may also impede musculoskeletal development.…”
Section: Introductionmentioning
confidence: 99%